Smart Face-shield Berteknologi Internet of Things sebagai Alat Pelindung Diri di Era Pandemi Covid-19 - Berlilana Berlilana; Bagus Adhi Kusuma; Fikri Ramadhan (STMIK Budi Darma, 2021)
Covid-19 or Corona is a pandemic virus that has spread in almost all parts of the world. The speed of transmission of this virus is a major problem. This virus can be spread quickly through coughing, sneezing, talking, which essentially can expel droplets because this virus mostly has a host in droplets. The face area can easily be infected with Covid-19, for example entering through the eyes, nose or mouth. In this era of a pandemic, there are so many OTG or people without symptoms that it becomes a problem in suppressing this disease. There are also people with fever symptoms which are one of the indications for corona disease but are not necessarily positive, they must go through initial screening such as rapid tests and PCR (Polymerase Chain Reaction) to more accurately identify someone exposed to Covid-19 or not. In the era of the new normal pandemic, it is very difficult to trace someone's contact with anyone, especially if there is one patient who is positive for Covid-19. Therefore, the purpose of this research is proposed, namely to create a tool that essentially functions as a tool for social distancing reminders that is integrated in an PPE, namely Face-Shield. This face-shield has an RGB camera, thermal camera and proximity sensor. The distance measurement method uses the ultrasonic wave ping principle which will detect a distance between humans of about 1 meter. The AMD 8833 thermal camera detects the ambient temperature and the RGB camera to display an image of the environment if needed via a computer connection. In order to facilitate data monitoring, Android smartphones are also integrated with this system to view temperature and distance data via an Internet connection. The results of the tests carried out using black-box testing of all component devices run properly